Modelling the Severity of Plastic Shrinkage in Cementitious Materials - Sayahi, Faez; Emborg, Mats; Hedlund, Hans; Cwirzen, Andrzej; Stelmarczyk, Marcin (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2020)
Plastic shrinkage cracking in cement-based materials occurs between the mixing and the final setting of the mixture, where rapid evaporation of the mixed water is the main cause behind the phenomenon. The induced cracks may impair the durability and sustainability of the structure by facilitating ingress of harmful materials into the concrete bulk. In this paper a new model for estimating the cracking severity of plastic cementitious materials is presented based on the mixture’s initial setting time and the amount of the pore liquid evaporated from within the concrete mass. Results of experiments performed by the authors in another study, in addition to results of tests performed by other researchers are used to control the validity of the model. It is concluded that the model can anticipate the cracking severity of plastic concretes with good precision. The new method can provide practical tools for designers and contractors to predict and compare the cracking risk of the concretes prior to casting.